Insight into the mechanisms and functions of spliceosomal snRNA pseudouridylation - Adachi, Hironori (World J Biol Chem, 2014)
Pseudouridines (Ψs) are the most abundant and highly conserved modified nucleotides found in various stable RNAs of all organisms. Most Ψs are clustered in regions that are functionally important for pre-mRNA splicing. Ψ has an extra hydrogen bond donor that endows RNA molecules with distinct properties that contribute significantly to RNA-mediated cellular processes. Experimental data indicate that spliceosomal snRNA pseudouridylation can be catalyzed by both RNA-dependent and RNA-independent mechanisms. Recent work has also demonstrated that pseudouridylation can be induced at novel positions under stress conditions, suggesting a regulatory role for Ψ.